Investment barriers in the European Union 2023 - European Investment Bank (European Investment Bank, 2024)
Discover key insights from the Investment barriers report 2023, an authoritative assessment by the European Investment Bank Group on investment hurdles in the European Union. The report underscores the pivotal role of investment in the economy while meticulously detailing the constraints that impede investment at the national and EU level. This year’s report takes a particular look at the role of commercial power purchase agreements in renewable energy projects, climate resilience investments in transport systems, antimicrobial resistance, the forestry sector, and cross-border infrastructure projects. It is an essential read for anyone looking to understand the investment landscape within the European Union.